Which Factors Are Priced? An Application of the Fama French Three‐Factor Model in Australia. Issue 4 (28th November 2015) - Vo, Duc Hong
Abstract : Various empirical studies on the application of the Fama French three‐factor model have been attempted and the conclusions are mixed on which factors from the model are priced in the Australian context. Different approaches to portfolio formations have been adopted in different studies. This empirical study is conducted to examine the robustness of the estimates under various approaches to portfolio formation and to provide additional evidence on the debate of the "relevance" of the Fama French three‐factor model in Australian regulatory decisions. Using the Fama and MacBeth (1973)'s two‐stage cross‐sectional regression technique on the period of five years, the standard Australian regulatory cycle, from July 2009 to May 2014, the findings from this study are mixed. It is argued that while the application of the Fama French three‐factor model is interesting for research endeavour, the adoption of this model into public policy is problematic and as such, not recommended.